The paradox of death and the Theatre of the Absurd - Klimczak , Dariusz Piotr (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
The aim of the article is the presentation of some interesting and stimulating questions connected with the problem of eschatological codes in the Theatre of the Absurd. The main objective of this paper is to discuss the topos of Death in the Theatre of the Absurd. Because the subject has been underexplored so far, the author tries to triangulate the Theatre of the Absurd within the genre of drama first, and then moves on to the short reflection on chosen plays of Beckett and Ionesco, concentrating on the role that eschatological elements, funereal objects and eschatons play in them. The starting point of this paper could be called “eschatology of the Absurd” or “immortality deconstructed”. Meaninglessness, as the value of absolute meaning, the meaning (Sinn) and significance (Bedeutung) of Death in the Theatre of the Absurd, is also discussed. As a method of research, he proposes a short “collective phenomenological analysis”. To analyse the issue from a broad perspective, the author takes into account the relationships between the writers and their times, and refers to cultural sources, specifically the Paradox of Death in the Theatre -particularly in the Theatre of the Absurd.